Characterization of the production of maguey in the District of Miahuatlán, Oaxaca - Cuevas Reyes, Venancio; Sánchez Toledano, Blanca I.; Borja Bravo, Mercedes; Espejel García, Anastacio; Sosa Montes, Mauricio; Barrera Rodríguez, Ariadna I.; Saavedra García, Máximo Jorge (Revista Mexicana de Ciencias Agrícolas, 2019)
The objective of this study is to characterize the maguey production system in the District of Miahuatlán with the purpose of identifying the types of producers and the characteristics that differentiate them. Stratified sampling was used to select a representative sample of 83 maguey producers from the District of Miahuatlán in the state of Oaxaca. With the use of multivariate methods, three types of producers were identified; subsistence producers (n = 36, 44.4%), producers of low productive scale (n = 31, 38.3%) and producers of medium scale (n = 14, 17.3%). The study shows that the production of maguey is done in a traditional way, although a large number of producers perform the preparation of the land with machinery (between 38.5 and 67.9%), a small number of them have technical assistance (between 25 and 39%) and less than 15.4% carry out the certification of the maguey plantations. It is concluded that more than 70% of the production of maguey obtained by small producers is integrated into mezcal production, which demands differentiated support strategies to improve production processes by types of producers and maintain mezcal production in a traditional, which improves the income of the small family units that maintain the production of this drink.
Keywords: mezcal; problematic; traditional production; typology of producers